2021
DOI: 10.3897/neobiota.69.71949
|View full text |Cite
|
Sign up to set email alerts
|

Non-native plant drives the spatial dynamics of its herbivores: the case of black locust (Robinia pseudoacacia) in Europe

Abstract: Non-native plants typically benefit from enemy release following their naturalization in non-native habitats. However, over time, herbivorous insects specializing on such plants may invade from the native range and thereby diminish the benefits of enemy release that these plants may experience. In this study, we compare rates of invasion spread across Europe of three North American insect folivores: the Lepidoptera leaf miners Macrosaccus robiniella and Parectopa robiniella, and the gall midge Obolodiplosis ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Although there are relatively few stands of black locust in the area studied (Ciuvăț et al, 2013), the species is frequently cultivated in parks, along roadsides, in home gardens, on abandoned agricultural land, etc., which explains why three of the four most common alien insect species (detected at more than 20 observation points) were those associated with R. pseudoacacia. Recently, Mally et al, (2021) found that the spatial distribution of the black locust is the most consistent predictor of the spread of P. robiniella, M. robiniella and O. robiniae in Europe. On the other hand, two of the species found at a very small number of observation sites, G. cooleyi and E. strobus, live on Douglas fir and eastern white pine, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are relatively few stands of black locust in the area studied (Ciuvăț et al, 2013), the species is frequently cultivated in parks, along roadsides, in home gardens, on abandoned agricultural land, etc., which explains why three of the four most common alien insect species (detected at more than 20 observation points) were those associated with R. pseudoacacia. Recently, Mally et al, (2021) found that the spatial distribution of the black locust is the most consistent predictor of the spread of P. robiniella, M. robiniella and O. robiniae in Europe. On the other hand, two of the species found at a very small number of observation sites, G. cooleyi and E. strobus, live on Douglas fir and eastern white pine, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…in which d is the distance between county i and each previously invaded county j (Mally et al 2021 ). The spatial contagion variable was estimated for each county in each year to account for annual changes in the invaded range of laurel wilt.…”
Section: Methodsmentioning
confidence: 99%
“…A number of species have invaded Europe from other continents, aided by human activity, and have often spread quickly over the continent, hostplant availability permitting. Examples are Macrosaccus robiniella (Clemens, 1859) and Parectopa robiniella Clemens, 1863 that invaded Europe probably with the aid of airplanes in the 1970s or 1980s of the last century, and which have since spread over a large part of Europe, finding their hostplant Robinia pseudoacacia L. widely distributed (Mally et al 2021). Two North American leafminers of walnuts and related Juglandaceae were recently noted for the first time respectively in Italy (Coptodisca lucifluella (Clemens, 1860)) (Bernardo et al 2011(Bernardo et al , 2015 and Hungary (C. juglandiella (Chambers, 1874)) (Takács et al 2020), and both have since also been found in neighbouring countries, suggesting spread through dispersal (Takács et al 2020;Tomov 2020;Haslberger and Segerer 2021;Huemer 2021;Laštůvka et al 2021).…”
Section: Introductionmentioning
confidence: 99%